TESTING METHODS OF KNOWLEDGE ON THE BASIS OF NEURAL NETWORK - Artur A. Mitsel; Aleksey A. Poguda; Konstantin A. Semenov; Anastasia E. Utesheva (Открытое образование (Москва), 2016)
The methods of testing students’ knowledge and ability to assess the responses to the example of the humanities. These methods are based on a combination of traditional testing methods and apparatus using neural networks. Uniqueness of algorithm allows to use it in various spheres of the analysis of natural language texts.